Does GCG Implementation in BWUT (Badan Wakaf Uang Tunai) MUI DIY Affect Waqifs Trust? (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2022)
In 2019 BWUT MUI DIY managed to raise waqf funds of Rp.627,352,991 with a wakif number of 1854 people. But there is a difference in increased Rp. 27,352,991 of 174 wakifs in 2 years by BWUT MUI DIY. These problems are influenced by professionalism in the management of cash waqf. In addition, there is still the management of waqf institutions that are less than ideal and by GCG principles. This study aimed to determine the effect of each direction of GCG in waqf management on wakif trust. This research is quantitative by sample waqf in BWUT MUI DIY. The data was obtained by questionnaire and analyzed using SEM-PLS supported by the SmartPLS 3.0 application software. The findings in this study indicate that the transparency variable has three t-statistics greater than 1.64, so it can be identified as significant to wakif trust. While the independency variable has an OSE value of -0.341 which means it is negative with a t-statistic greater than 1.64, this result indicates that the better the implementation of independence. And the accountability variable does not affect wakif trust by a t-statistic value of 0.458. However, the transparency variable can be interpreted that the better the implementation of the GCG principle in the waqf institution impacted to increasing the level of wakif trust.